Comparative effectiveness of nipple-sparing mastectomy and breast-conserving surgery on long-term prognosis in breast cancer - Chen, Qitong; Qu, Limeng; He, Yeqing; Deng, Yueqiong; Zhou, Qin; Yi, Wenjun (Frontiers in Endocrinology, 2023)
Background: The frequency of nipple-sparing mastectomy (NSM) surgery is currently increasing. Nonetheless, there is a paucity of long-term prognosis data on NSM. This study compared the long-standing prognosis of NSM in relation to breast-conserving surgery (BCS). Methods: Population-level data for 438,588 female breast cancer patients treated with NSM or BCS and postoperative radiation from 2000 to 2018 were identified in the Surveillance, Epidemiology, and End Results (SEER) database; 321 patients from the Second Xiangya Hospital of Central South University were also included. We performed propensity score matching (PSM) to reduce the influence of selection bias and confounding variables to make valid comparisons. Kaplan‒Meier analysis, log-rank test, and Cox regression were applied to analyze data. Results: There were no significant differences in long-term survival rates between patients who underwent NSM and those who underwent BCS+RT, as indicated by the lack of significant differences in overall survival (OS) (P=0.566) and breast cancer-specific survival (BCSS) (P=0.431). Cox regression indicated that NSM and BCS+RT had comparable prognostic values (P=0.286) after adjusting for other clinicopathological characteristics. For OS and BCSS, subgroup analysis showed that the majority of patients achieved an analogous prognosis whether they underwent NSM or BCS. The groups had comparable recurrence-free survival (RFS), with no significant difference found (P=0.873). Conclusions: This study offers valuable insights into the long-term safety and comparative effectiveness of NSM and BCS in the treatment of breast cancer. These findings can assist clinicians in making informed decisions on a case-by-case basis.